Kajian Prinsip Kerja Sama pada Tindak Tutur Transaksional di Depo Air Minum Isi Ulang Sehat Lestari - Taufiq Hidayat; Taswirul Afkar; Seftia Wulan Ayu Ningrum; Falah Arifbillah Subagio (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to examine the realization of Grice’s cooperative principles in transactional speech acts between sellers and buyers at the Depo Air Minum Isi Ulang Sehat Lestari (Healthy Refill Drinking Water Depot). The cooperative principles consist of four maxims: quantity, quality, relevance, and manner. The research is motivated by the importance of effective communication in sales interactions, particularly to avoid misunderstandings in conveying intentions and information. A qualitative descriptive method was employed, with data collected through participatory observation and recorded conversations. The findings indicate that all four maxims were naturally realized in daily interactions. Utterances such as “Mas, air satu” (“One gallon, please”), “Air galon segar loh” (“The water is fresh”), and “Tolong kirim air 10 galon” (“Please deliver 10 gallons”) reflect contextually appropriate and functionally effective applications of the maxims. Furthermore, the use of concise, clear, and straightforward speech structures shows that the cooperative principles are not only evident in content but also in the linguistic form used. These findings highlight that communication in micro-level services such as water refill depots tends to be pragmatic, efficient, and shaped by local social norms and contextual understanding.